Sagittal Distal Tibial Articular Angle and the Relationship to Talar Subluxation in Total Ankle Arthroplasty. (September 2016) - Veljkovic, Andrea; Norton, Adam; Salat, Peter; Abbas, Kaniza Zahra; Saltzman, Charles; Femino, John E.; Phisitkul, Phinit; Amendola, Annunziato
Background: Longevity of total ankle replacement (TAR) depends heavily on anatomic alignment. The lateral talar station (LTS) classifies the sagittal position of the talus relative to the tibia. We hypothesized that correcting the sagittal distal tibial articular angle (sDTAA) during TAR would anatomically realign the tibiotalar joint and potentially reduce the risk of prosthesis subluxation. Methods: The LTS (millimeters) and sDTAA (degrees) were measured twice by 2 blinded observers using weight-bearing lateral ankle radiographs obtained before (n = 96) and after (n = 94) TAR, with excellent interobserver and intraobserver reliability (correlation coefficient >0.9). Results: Preoperative LTS was as follows: anterior (60.4%), posterior (27.1%), and neutral (12.5%). A strong preoperative correlation was found between LTS and sDTAA ( r = 0.81; P < .0001). In ankles that were initially anterior and became less anterior postoperatively (n = 41), LTS decreased from an average 8.1 mm to 6.5 mm and the LTS changed 1.1 mm per degree of sDTAA change. In ankles that were initially posterior (n = 25), LTS increased from an average of −5.1 mm to −2.8 mm and the LTS changed 0.6 mm per degree of sDTAA change. The correlation between LTS and sDTAA was reduced postoperatively ( r = 0.62; P < .0001). Conclusions: Our results suggest that rather than following generic recommendations, the surgeon should customize the sagittal distal tibial cut to the individual patient based on the preoperative LTS in order to achieve neutral TAR alignment. Level of Evidence: Level III, retrospective comparative series.